Method for manufacturing double-sided metal-clad laminate and method for manufacturing circuit board

By incorporating a filler-containing layer with a metal salt of organic phosphinic acid in the manufacturing process of double-sided metal-clad laminates, the method addresses the issue of low interlayer adhesion, achieving improved reliability and reduced transmission losses.

JP2025058625APending Publication Date: 2025-04-09NIPPON STEEL CHEM & MATERIAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023168667
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-04-09

AI Technical Summary

Technical Problem

Existing double-sided metal-clad laminates face challenges with low interlayer adhesion between the adhesive layer and the insulating resin layer, leading to potential delamination during circuit processing.

Method used

A method for manufacturing a double-sided metal-clad laminate involves forming a filler-containing layer with a metal salt of organic phosphinic acid on a single-sided metal-clad laminate, and then bonding these layers together to enhance adhesion.

Benefits of technology

The proposed method significantly improves the interlayer adhesion, reduces transmission losses at high frequencies, and prevents delamination during circuit processing, thereby enhancing the reliability of the circuit board.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025058625000001_ABST
    Figure 2025058625000001_ABST
Patent Text Reader

Abstract

To provide a method for manufacturing a double-sided metal-clad laminate which improves adhesion between an adhesive layer and an insulation resin layer, and has the adhesive layer and the insulation resin layer.SOLUTION: A method: forms filler-containing layers AD1 and AD2 on each of an insulation resin layer R1 of a first metal-clad laminate C1 and an insulation resin layer R2 of a second metal-clad laminate C2; then arranges the filler-containing layers AD1 and AD2 so as to be brought into contact with each other; thermo-compression bonds a metal-clad laminate C1' with the filler-containing layer and a metal-clad laminate C2' with the filler-containing layer; and manufactures a double-sided metal-clad laminate C having the first metal-clad laminate C1, an adhesive layer AD and the second metal-clad laminate C2. The filler-containing layers AD1 and AD2 have polyimide containing 20 parts by mol or more of a diamine residue derived from dimer acid type diamine to 100 parts by mol of the total diamine residues, and a metal salt of an organic phosphinic acid, and the weight ratio of the metal salt of the organic phosphinic acid to the total filler-containing layers AD1 and AD2 is 28 wt.% or more and 47 wt.% or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a double-sided metal-clad laminate useful as a material for electronic components, and a method for producing a circuit board. [Background technology]

[0002] In recent years, with the progress of miniaturization, weight reduction, and space saving of electronic devices, there is an increasing demand for flexible printed circuits (FPCs) that are thin, lightweight, flexible, and have excellent durability even when repeatedly bent. Because FPCs allow three-dimensional and high-density mounting even in a limited space, their applications are expanding to include wiring for electronic devices such as HDDs, DVDs, and smartphones, as well as components such as cables and connectors.

[0003] In addition to the above-mentioned increase in density, the advancement of device performance has created a need to accommodate the increasing frequency of transmitted signals. When transmitting high-frequency signals, if there is a large transmission loss in the transmission path, problems such as loss of electrical signals and longer signal delay times will occur. Therefore, reducing transmission loss will also be important in the future for FPCs.

[0004] In order to reduce transmission loss, it is effective to increase the thickness of the dielectric layer as well as improve the dielectric properties of the dielectric layer. Patent Document 1 proposes that in order to lower the dielectric tangent and increase the thickness of the dielectric layer, a double-sided metal-clad laminate is manufactured by interposing a thick adhesive layer between the insulating resin layers of a pair of single-sided metal-clad laminates and thermocompression bonding the whole. In Patent Document 1, a thermally crosslinkable resin made from dimer acid diamine (DDA), which has excellent dielectric properties, is used as the material for the adhesive layer, and crosslinking is formed during thermocompression bonding to improve the heat resistance of the adhesive layer.

[0005] Also, Patent Document 2 considers a configuration in which an adhesive layer made of a thermoplastic resin or a thermosetting resin is used as a core layer and laminated between single-sided metal-clad laminates. Patent Document 3 considers a configuration in which no core layer is provided and the resin sides of single-sided metal-clad laminates are bonded together to laminate. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2018-170417 A [Patent Document 2] JP 2020-55299 A [Patent Document 3] International Publication No. WO2020 / 022129 Summary of the Invention [Problem to be solved by the invention]

[0007] In the method of using a resin sheet as an adhesive layer and bonding it to the insulating resin layer of a single-sided metal-clad laminate, as in Patent Document 1, there is a problem in that the adhesive layer has low polarity, resulting in low adhesion between the adhesive layer and the insulating resin layer, and an improvement in this regard was desired.

[0008] Therefore, the object of the present invention is to improve the interlayer adhesion between an adhesive layer and an insulating resin layer when manufacturing a double-sided metal-clad laminate in which a metal layer is laminated on both sides of a resin laminate having an adhesive layer and an insulating resin layer. [Means for solving the problem]

[0009] As a result of intensive research, the inventors have discovered that the above-mentioned problems can be solved by forming a filler-containing layer containing a high concentration of a metal salt of an organic phosphinic acid on a single-sided metal-clad laminate and laminating the filler-containing layers together in the manufacture of a double-sided metal-clad laminate, and have thus completed the present invention.

[0010] That is, the method for producing a double-sided metal-clad laminate of the present invention is a method for producing a double-sided metal-clad laminate in which metal layers are laminated on both sides of a resin laminate having an adhesive layer and an insulating resin layer. The method for producing a double-sided metal-clad laminate of the present invention includes the following steps 1 to 3; Step 1: A step of preparing a single-sided metal-clad laminate having a metal layer and an insulating resin layer laminated on at least one surface of the metal layer; Step 2: laminating a filler-containing layer on a surface of the insulating resin layer in the single-sided metal-clad laminate to produce a metal-clad laminate with a filler-containing layer; Step 3: a step of forming the adhesive layer by placing two of the metal-clad laminates with the filler-containing layer so that the filler-containing layers face each other and bonding them together to form a double-sided metal-clad laminate having metal layers on both sides of the resin laminate; Contains: In the method for producing a double-sided metal-clad laminate of the present invention, the filler-containing layer contains a polyimide containing a tetracarboxylic acid residue and a diamine residue, and a metal salt of an organic phosphinic acid, the polyimide contains 20 or more molar parts of a diamine residue derived from a dimer acid type diamine in which two terminal carboxylic acid residues of a dimer acid are substituted with a primary aminomethyl group or an amino group, relative to a total of 100 molar parts of the diamine residue; The filler-containing layer is characterized in that the weight ratio of the metal salt of the organic phosphinic acid to the entire filler-containing layer is within the range of 28% by weight to 47% by weight.

[0011] In the method for producing a double-sided metal-clad laminate of the present invention, the filler-containing layer in step 2 may be formed by applying and drying a resin composition containing the polyimide and the metal salt of the organic phosphinic acid onto the surface of the insulating resin layer.

[0012] The method for producing a double-sided metal-clad laminate of the present invention comprises the steps of: (i) mixing a portion of the polyimide with the metal salt of the organic phosphinic acid in an organic solvent and stirring to obtain a filler-dispersed resin solution; and (ii) mixing the remainder of the polyimide with an organic solvent into the filler-dispersed resin solution and stirring to obtain the resin composition; In this case, in the step (i), the weight ratio of the polyimide in the filler-dispersed resin solution may be set within a range of 3 to 15 parts by weight relative to 100 parts by weight of the final total amount of the polyimide, and the solid content concentration in the filler-dispersed resin solution may be adjusted within a range of 40 to 60% by weight, and in the step (ii), the weight ratio of the metal salt of the organic phosphinic acid in the resin composition may be set within a range of more than 40 parts by weight and not more than 90 parts by weight relative to 100 parts by weight of the final total amount of the polyimide.

[0013] In the method for producing a double-sided metal-clad laminate of the present invention, in the step 3, the two metal-clad laminates with the filler-containing layer may be temporarily pressure-bonded together, and then a heat treatment may be performed.

[0014] In the manufacturing method of the double-sided metal-clad laminate of the present invention, the insulating resin layer of the single-sided metal-clad laminate may have a multilayer structure in which a thermoplastic polyimide layer, a non-thermoplastic polyimide layer and a thermoplastic polyimide layer are laminated in this order.

[0015] The manufacturing method for the double-sided metal-clad laminate of the present invention may be such that the resin laminate is formed by laminating an insulating resin layer / adhesive layer / insulating resin layer in this order, and the adhesive layer is formed by bonding two of the filler-containing layers together to form an integrated body.

[0016] The method for producing a circuit board of the present invention includes a step of processing one or both of the metal layers in the double-sided metal-clad laminate produced by the above-mentioned method into wiring. Effect of the Invention

[0017] The method of the present invention makes it possible to provide a double-sided metal-clad laminate that can reduce transmission loss even at high frequencies, has high interlayer adhesion between the adhesive layer and the insulating resin layer, and can suppress delamination during circuit processing such as drilling and cutting. The double-sided metal-clad laminate obtained by the method of the present invention has high interlayer adhesion, and therefore can improve the reliability of circuit boards. [Brief description of the drawings]

[0018] [Figure 1] 1 is an explanatory diagram of main steps of a method for manufacturing a double-sided metal-clad laminate according to one embodiment of the present invention. FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS An embodiment of the present invention will be described with reference to the accompanying drawings.

[0020] FIG. 1 is an explanatory diagram showing the main steps of a method for producing a double-sided metal-clad laminate according to one embodiment of the present invention. The method for producing the double-sided metal-clad laminate C includes steps 1 to 3 described below, and is a method for producing a double-sided metal-clad laminate C having a layer structure in which a metal layer M1, an insulating resin layer R1, an adhesive layer AD, an insulating resin layer R2, and a metal layer M2 are laminated in this order, as shown in FIG. 1(4). The metal layer M1 and the metal layer M2, and the insulating resin layer R1 and the insulating resin layer R2 may have the same structure or different structures, but are preferably the same structure. The detailed structures of the metal layers M1 and M2, the insulating resin layers R1 and R2, and the adhesive layer AD will be described later.

[0021] Step 1: As shown in FIG. 1(1), a first metal-clad laminate C1 is prepared having a metal layer M1 that will become the first metal layer and an insulating resin layer R1 that will become the first insulating resin layer, and a second metal-clad laminate C2 is prepared having a metal layer M2 that will become the second metal layer and an insulating resin layer R2 that will become the second insulating resin layer.

[0022] The method for producing the first metal-clad laminate C1 and the second metal-clad laminate C2 in step 1 is not particularly limited, and may be, for example, a casting method in which a resin solution that will become the insulating resin layers R1, R2 is applied onto a metal foil that will become the metal layers M1, M2, or a lamination method in which a resin sheet that will become the insulating resin layers R1, R2 is laminated onto the metal foil.

[0023] As a preferred specific example of step 1, a case where a second metal-clad laminate C2 in which the insulating resin layer R2 is a single or multiple polyimide layers is produced by a casting method will be described. In this case, the second metal-clad laminate C2 is produced by the following steps (i) and (ii); (i) a step of applying a polyamic acid solution, which is a precursor of polyimide to be the insulating resin layer R2, onto a metal foil to be the metal layer M2 and drying the solution to form a coating film; (ii) a step of heat-treating the coating film to imidize the polyamic acid to obtain a second metal-clad laminate C2 having an insulating resin layer R2; This can be carried out by: The first metal-clad laminate C1 can be produced in the same manner according to steps (i) and (ii).

[0024] The polyamic acid solution used in step (i) can be produced by reacting an acid dianhydride component and a diamine component in a solvent. Specifically, the acid dianhydride component and the diamine component are dissolved in an organic solvent in a molar ratio of about 0.8 to 1.2, and the mixture is stirred at a temperature in the range of 0 to 100°C for 30 minutes to 24 hours to cause a polymerization reaction, thereby synthesizing a polyamic acid. In this reaction, the reaction components are dissolved in the organic solvent so that the resulting polyamic acid is in the range of 5 to 30% by weight, preferably 10 to 20% by weight. Examples of organic solvents used in the polymerization reaction include N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), N,N-diethylacetamide, N-methyl-2-pyrrolidone (NMP), 2-butanone, dimethylsulfoxide (DMSO), hexamethylphosphoramide, N-methylcaprolactam, dimethyl sulfate, cyclohexanone, dioxane, tetrahydrofuran, diglyme, triglyme, and cresol. Two or more of these solvents can be used in combination, and aromatic hydrocarbons such as xylene and toluene can also be used in combination. The amount of organic solvent used is not particularly limited, but it is preferable to adjust the concentration of the polyamic acid solution obtained by the polymerization reaction to about 5 to 30% by weight. The obtained polyamic acid solution can be used as it is in step (i), but it can be concentrated, diluted, or replaced with another organic solvent as necessary.

[0025] In step (i), the method for applying the polyamic acid solution onto the metal foil is not particularly limited, and it is possible to apply it using a coater such as a comma, die, knife, or lip coater. The viscosity of the polyamic acid solution is preferably adjusted to within the range of 500 mPa·s to 100,000 mPa·s. If it is outside this range, defects such as uneven thickness and streaks are likely to occur in the film during the coating operation using a coater or the like.

[0026] When the insulating resin layer R2 is composed of multiple polyimide layers, in step (i), the coating and drying of different types of polyamic acid solutions may be repeated multiple times, or different types of polyamic acid solutions may be simultaneously coated and dried in a multi-layer laminated state by multi-layer extrusion.

[0027] The conditions for imidization in step (ii) are not particularly limited, and for example, a heat treatment is preferably performed by heating for 0.1 to 24 hours at a temperature in the range of 80 to 400° C. When the insulating resin layer R2 is composed of a plurality of polyimide layers, the layers can be imidized collectively in step (ii).

[0028] Step 2: 1(2), this step is a step of forming filler-containing layers AD1, AD2 on the insulating resin layer R1 of the first metal-clad laminate C1 and on the insulating resin layer R2 of the second metal-clad laminate C2, respectively. The first metal-clad laminate C1 having the filler-containing layer AD1 is referred to as the metal-clad laminate C1' with a filler-containing layer, and the second metal-clad laminate C2 having the filler-containing layer AD2 is referred to as the metal-clad laminate C2' with a filler-containing layer.

[0029] The filler-containing layers AD1, AD2 can be formed by a casting method or a laminating method, but are preferably formed by a casting method because this increases the adhesion at the interface between the insulating resin layers R1, R2 and the adhesive layer AD. In the case of the casting method, a resin composition is applied onto the insulating resin layer R1 of the first metal-clad laminate C1, heat-treated, and dried to form a filler-containing layer AD1 that will become a part of the adhesive layer AD. Also, a resin composition is applied onto the insulating resin layer R2 of the second metal-clad laminate C2, heat-treated, and dried to form a filler-containing layer AD2 that will become a part of the adhesive layer AD. In the case of the lamination method, the resin composition is applied onto an arbitrary substrate, dried, and then peeled off from the substrate to form an adhesive sheet that becomes the filler-containing layers AD1 and AD2. This adhesive sheet is laminated onto the insulating resin layer R1 of the first metal-clad laminate C1 and onto the insulating resin layer R2 of the second metal-clad laminate C2. The arbitrary substrate is not particularly limited as long as the adhesive sheet can be easily peeled off, and it is preferable to use, for example, a metal foil such as copper foil, a resin sheet, etc. As the resin composition used in this process, for example, a solution containing a polyimide and a metal salt of an organic phosphinic acid can be used. Details of this resin composition will be described later. The method of applying the resin composition onto the insulating resin layers R1 and R2 or onto the arbitrary substrate is not particularly limited, and it is possible to apply it with a coater such as a comma, a die, a knife, or a lip.

[0030] The filler-containing layers AD1 and AD2 contain a metal salt of an organic phosphinic acid as a filler component. By blending a high concentration of the metal salt of an organic phosphinic acid, the adhesion between layers can be improved. In order to fully exert such an effect, the weight ratio of the metal salt of an organic phosphinic acid to the entire filler-containing layer AD1 or the entire filler-containing layer AD2 is in the range of 28% by weight to 47% by weight, and preferably in the range of 30% by weight to 40% by weight. If the weight ratio of the metal salt of an organic phosphinic acid is less than 28% by weight, the adhesion between the adhesive layer AD and the insulating resin layers R1 and R2 is not fully exerted, and if it exceeds 47% by weight, the elongation of the adhesive layer AD when it is formed may decrease or the dielectric properties may deteriorate. Preferably, 80% by weight or more of the filler component is a metal salt of an organic phosphinic acid, more preferably 90% by weight or more, and most preferably 95 to 100% by weight. The metal salt of an organic phosphinic acid will be described in detail later. Furthermore, from the viewpoint of exhibiting the adhesiveness between the adhesive layer AD and the insulating resin layers R1 and R2, the weight ratio of the filler component to the total amount of 100 parts by weight of the resin components is preferably in the range of more than 40 parts by weight and not more than 110 parts by weight, more preferably in the range of more than 40 parts by weight and not more than 100 parts by weight, and most preferably in the range of 45 to 90 parts by weight. If the weight ratio of the filler component is 40 parts by weight or less, the adhesiveness between the adhesive layer AD and the insulating resin layers R1 and R2 is not sufficiently exhibited, and if it exceeds 110 parts by weight, the elongation when the adhesive layer AD is formed may decrease or the dielectric properties may deteriorate. Also, from the viewpoint of exhibiting the effect of the invention sufficiently, the total amount of the resin component and the filler component is preferably 80% by weight or more, more preferably 90% by weight or more, and most preferably 95 to 100% by weight, based on the total solid content in the resin composition. In the present invention, the "solid content" means the remainder excluding the solvent.

[0031] The thickness of the filler-containing layers AD1 and AD2 is preferably within the range of 12 to 75 μm, and more preferably within the range of 25 to 75 μm. If the thickness of the filler-containing layers AD1 and AD2 is less than 12 μm, the dielectric loss tangent is insufficient, and if it exceeds 75 μm, the thickness variation becomes large. The thickness of the filler-containing layers AD1 and AD2 may be the same or different.

[0032] In this embodiment, the first heat treatment conditions for drying the resin composition after applying it to the insulating resin layers R1, R2 or any substrate can be, for example, a temperature in the range of 80 to 160°C and a time of 3 to 20 minutes, preferably 5 to 10 minutes. In this step 2, the drying is performed in an open state of the filler-containing layers AD1, AD2, respectively, so that the solvent in the filler-containing layers AD1, AD2 and the condensed water generated by the crosslinking reaction can be volatilized outside the film, and efficiently removed in a short time. In addition, since the thickness of the filler-containing layers AD1, AD2 is thinner than that of the adhesive layer AD, the volatilization of the solvent and the condensed water generated by the crosslinking reaction outside the film proceeds efficiently. If the drying temperature is less than 80°C or the drying time is less than 3 minutes, the removal of the solvent from the filler-containing layers AD1, AD2 is insufficient, and for example, blisters, peeling, etc. are likely to occur due to the heat treatment in the flow process and reflow process, and the crosslinking reaction proceeds insufficiently, and the effect of improving the dielectric tangent cannot be obtained. On the other hand, if the drying temperature exceeds 160° C. or the drying time exceeds 20 minutes, the crosslinking reaction will proceed too far, and the adhesion between the adhesive layer AD and the insulating resin layer R1 and the insulating resin layer R2 in the double-sided metal-clad laminate C will be likely to decrease.

[0033] Step 3: As shown in FIG. 1(3), the filler-containing layers AD1 and AD2 are arranged so as to abut against each other, and the metal-clad laminate C1' with the filler-containing layer and the metal-clad laminate C2' with the filler-containing layer are temporarily pressed together, and then heat-treated under the second heat treatment conditions to form a double-sided metal-clad laminate C having the first metal-clad laminate C1, the adhesive layer AD (a layer in which the filler-containing layer AD1 and the filler-containing layer AD2 are bonded together), and the second metal-clad laminate C2. In addition, when the filler-containing layers AD1 and AD2 contain a crosslinking agent, the second heat treatment after the temporary pressing completes the crosslinking of the thermally crosslinkable resin in the filler-containing layers AD1 and AD2. This advances the entanglement of polymer chains at the interface between the insulating resin layer R2 and the adhesive layer AD, improving adhesion.

[0034] The temperature for the temporary pressure bonding is, for example, within a range of 70 to 120° C., and preferably within a range of 80 to 100° C. If the temperature for the temporary pressure bonding is below the above range, the filler-containing layer AD1 and the filler-containing layer AD2 will not be temporarily pressure bonded to each other, and if the temperature exceeds the above range, wrinkles may occur in the double-sided metal-clad laminate C. The pressure of the temporary pressure bonding is, for example, in the range of 0.2 to 1.0 MPa, and preferably in the range of 0.3 to 0.7 MPa. If the pressure of the temporary pressure bonding is less than 0.2 MPa, sufficient interlayer adhesion cannot be obtained, and if it exceeds 1.0 MPa, wrinkles may occur in the double-sided metal-clad laminate C. The time for temporary pressure bonding is not particularly limited, but is preferably within a range of 0.5 seconds to 1 minute, and more preferably within a range of 1 second to 5 seconds, so as not to complete the crosslinking reaction of the thermally crosslinkable resin.

[0035] The temperature of the second heat treatment is, for example, within a range of 150 to 250° C., and preferably within a range of 160 to 200° C. If the temperature of the second heat treatment is below the above range, the crosslinking reaction of the thermally crosslinkable resin may not be completed, resulting in insufficient heat resistance of the adhesive layer AD, or insufficient entanglement of polymer chains at the interfaces between the insulating resin layers R1, R2 and the adhesive layer AD, resulting in reduced adhesion between the layers. If the temperature exceeds the above range, it is disadvantageous in terms of energy efficiency. The time of the second heat treatment is, for example, within the range of 4 to 150 hours, and preferably within the range of 48 to 120 hours. If the time of the second heat treatment is less than the above range, the crosslinking reaction of the thermal crosslinking resin is not completed, the heat resistance of the adhesive layer AD may be insufficient, or the entanglement of the polymer chains at the interface between the insulating resin layers R1, R2 and the adhesive layer AD may be insufficient, resulting in a decrease in the adhesion between the layers, and if the time exceeds the above range, it is disadvantageous in terms of energy efficiency. In addition, the second heat treatment can be performed under atmospheric pressure without pressurization, or under vacuum.

[0036] In this embodiment, steps 2 and 3 can be carried out by a roll-to-roll method, which is preferable because it can improve productivity.

[0037] [Resin composition] Next, the resin composition used in step 2 will be described. The resin composition preferably contains a solvent-soluble polyimide as a resin component, a metal salt of an organic phosphinic acid as a filler component, and an organic solvent. The polyimide and the metal salt of an organic phosphinic acid will be described later as components of the adhesive layer AD. The organic solvent is not particularly limited as long as it can dissolve the polyimide, and examples thereof include N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), N,N-diethylacetamide, N-methyl-2-pyrrolidone (NMP), 2-butanone, dimethylsulfoxide (DMSO), hexamethylphosphoramide, N-methylcaprolactam, dimethyl sulfate, cyclohexanone, methylcyclohexane, dioxane, tetrahydrofuran, diglyme, triglyme, methanol, ethanol, benzyl alcohol, cresol, and acetone. Two or more of these organic solvents can be used in combination, and aromatic hydrocarbons such as xylene and toluene can also be used in combination.

[0038] From the viewpoint of developing adhesion between the adhesive layer AD and the insulating resin layers R1 and R2, the weight ratio of the metal salt of organic phosphinic acid to the total solid content in the resin composition is in the range of 28% by weight to 47% by weight, and preferably in the range of 30% by weight to 40% by weight. If the weight ratio of the metal salt of organic phosphinic acid is less than 28% by weight, the adhesion between the adhesive layer AD and the insulating resin layers R1 and R2 is not developed sufficiently, and if it exceeds 47% by weight, the elongation of the adhesive layer AD when it is formed may decrease, or the dielectric properties may deteriorate. From the same viewpoint, the weight ratio of the filler component to the total amount of the resin components (100 parts by weight) is preferably in the range of more than 40 parts by weight and not more than 110 parts by weight, more preferably in the range of more than 40 parts by weight and not more than 100 parts by weight, and most preferably in the range of 45 to 90 parts by weight. If the weight ratio of the filler component is 40 parts by weight or less, the adhesion between the adhesive layer AD and the insulating resin layers R1 and R2 is not sufficiently exhibited, and if it exceeds 90 parts by weight, the elongation when the adhesive layer AD is formed may decrease or the dielectric properties may deteriorate. From the viewpoint of fully exhibiting the effects of the invention, the total amount of the resin components and the filler components is preferably 80% by weight or more, more preferably 90% by weight or more, and most preferably 95 to 100% by weight, based on the total solid content in the resin composition.

[0039] In addition, when a polyimide having a ketone group in the molecule is used as the resin component, the resin composition preferably further contains a crosslinking agent having a functional group that undergoes a nucleophilic reaction with the ketone group. Here, the details of the polyimide having a ketone group in the molecule and the crosslinking agent will be described later. The resin composition preferably contains a crosslinking agent so that the functional group of the crosslinking agent is in the range of 0.04 to 0.50 mol, preferably 0.06 to 0.40 mol, in total, per 1 mol of ketone group contained in the polyimide. For example, when an amino compound for crosslinking is used as the crosslinking agent, the primary amino group can be in the range of 0.04 to 0.50 mol, preferably 0.06 to 0.40 mol, in total, per 1 mol of ketone group. If the functional group of the crosslinking agent is less than 0.04 mol in total per 1 mol of ketone group, crosslinking does not proceed sufficiently, and heat resistance after curing tends to be difficult to be expressed. On the other hand, if it exceeds 0.5 mol, the dielectric loss tangent tends to increase. This is presumably because the excess crosslinking agent restricts the mobility of the polyimide molecular chains, preventing the formation of an ordered molecular chain structure that is effective in suppressing the dielectric tangent during curing. Also, if the amount of crosslinking agent is too large, the unreacted crosslinking agent acts as a thermoplasticizer, which tends to reduce the heat resistance of the adhesive layer AD.

[0040] The viscosity of the resin composition is not particularly limited as long as it is a viscosity that allows coating, but for example, it is preferably in the range of 500 mPa·s to 100,000 mPa·s, and more preferably in the range of 1,000 mPa·s to 5,000 mPa·s. If it is outside this range, defects such as uneven thickness and streaks are likely to occur in the adhesive film during the coating operation. In addition, the solid content concentration in the resin composition is preferably in the range of 30 to 40 wt%, and more preferably in the range of 33 to 37 wt%.

[0041] The resin composition may contain, as optional components, as appropriate, within the scope of not impairing the effects of the invention, such as plasticizers, other curable resin components such as epoxy resins, curing agents, curing accelerators, organic or inorganic fillers other than metal salts of organic phosphinic acids, coupling agents, dispersants, and the like.

[0042] The resin composition can be produced by the following steps (i) and (ii); (i) a step of mixing a part of the resin component and a filler component in an organic solvent and stirring to obtain a filler dispersion; And, (ii) a step of mixing the remainder of the resin component with an organic solvent into the filler dispersion and stirring to obtain a resin composition; It is preferred to prepare the composition by a method comprising the steps of:

[0043] In step (i), the weight ratio of the resin content in the filler dispersion is adjusted to within the range of 3 to 15 parts by weight relative to the final total amount of the resin content of 100 parts by weight, and the solid content concentration in the filler dispersion is adjusted to within the range of 40 to 60% by weight. If the weight ratio of the resin content in the filler dispersion obtained in step (i) is less than 3 parts by weight relative to the final total amount of the resin content of 100 parts by weight, or if the solid content concentration exceeds 60% by weight, it becomes difficult to uniformly disperse the filler component, and aggregation occurs. On the other hand, if the weight ratio of the resin content in the filler dispersion obtained in step (i) is more than 15 parts by weight relative to the final total amount of the resin content of 100 parts by weight, or if the solid content concentration is less than 40% by weight, it becomes difficult to blend the filler component at a high concentration of more than 40 parts by weight relative to the final total amount of the resin content of 100 parts by weight in step (ii).

[0044] In step (ii), the weight ratio of the filler component in the resin composition is adjusted to be within the range of more than 40 parts by weight and not more than 90 parts by weight relative to 100 parts by weight of the final total amount of the resin components, and the solid content concentration in the resin composition is adjusted to be within the range of 30 to 40% by weight. The organic solvent used in steps (i) and (ii) may be the same as the organic solvent described for the resin composition.

[0045] According to the method for producing the resin composition, by blending the resin component in multiple stages and adjusting the solid content concentration, it is possible to blend a high concentration of filler component of more than 40 parts by weight per 100 parts by weight of the final total amount of the resin component without blending a dispersant and without causing aggregation, and when the adhesive layer AD or adhesive sheet is formed, both low dielectric tangent and interlayer adhesion are achieved. The resin composition obtained by the manufacturing method of this embodiment does not require a dispersant, so it does not need to contain substantially no dispersant. However, it is not prohibited to blend a dispersant to a range that does not significantly affect the dielectric properties. Note that "substantially does not contain a dispersant" means, for example, an amount less than 1.0 part by weight, preferably an amount of 0.1 part by weight or less, relative to 1.0 part by weight, which is the minimum amount of dispersant required to well disperse 100 parts by weight of the filler component.

[0046] [Composition of double-sided metal-clad laminate] The structure of the double-sided metal-clad laminate C manufactured as described above will now be described.

[0047] (metal layer) The material of the metal layer M1 and the metal layer M2 is not particularly limited, but examples thereof include copper, stainless steel, iron, nickel, beryllium, aluminum, zinc, indium, silver, gold, tin, zirconium, tantalum, titanium, lead, magnesium, manganese, and alloys thereof. Among these, copper or a copper alloy is particularly preferable. The material of the wiring layer in the circuit board of this embodiment, which will be described later, is the same as that of the metal layer M1 and the metal layer M2.

[0048] The thickness of the metal layer M1 and the metal layer M2 is not particularly limited, but when a metal foil such as copper foil is used, it is preferably 35 μm or less, more preferably in the range of 5 to 25 μm. From the viewpoint of production stability and handling, the lower limit of the thickness of the metal foil is preferably 5 μm. When a copper foil is used, it may be a rolled copper foil or an electrolytic copper foil. In addition, a commercially available copper foil may be used as the copper foil.

[0049] The metal foil may be subjected to a surface treatment using, for example, siding, aluminum alcoholate, aluminum chelate, a silane coupling agent, or the like, for the purpose of, for example, rust prevention or improving adhesive strength.

[0050] (insulating resin layer) The insulating resin layer R1 and the insulating resin layer R2 are not particularly limited as long as they are made of a resin having electrical insulation properties, and examples thereof include polyimide, liquid crystal polymer, epoxy resin, phenolic resin, polyethylene, polypropylene, polytetrafluoroethylene, silicone, ETFE, etc., but are preferably made of polyimide. Note that, in the present invention, the term "polyimide" refers to a resin made of a polymer having an imide group in the molecular structure, such as polyamideimide, polyetherimide, polyesterimide, polysiloxaneimide, polybenzimidazoleimide, etc.

[0051] Furthermore, the insulating resin layer R1 and the insulating resin layer R2 are not limited to a single layer, and may be a laminate of a plurality of resin layers.

[0052] The insulating resin layer R1 and the insulating resin layer R2 can be selected from, for example, commercially available polyimide films, commercially available liquid crystal polymer films, and resins used as insulating substrates in commercially available metal-clad laminates. Examples of polyimide films that can be used include UPILEX (trade name) manufactured by Ube Industries, Kapton (trade name) manufactured by Toray DuPont, Apical (trade name) and Pixio (trade name) manufactured by Kaneka Corporation, and examples of liquid crystal polymer films that can be used include Vecstar (trade name) manufactured by Kuraray Co., Ltd. and BIAC Film (trade name) manufactured by Primatec Co., Ltd.

[0053] The coefficient of thermal expansion (CTE) of the insulating resin layer R1 and the insulating resin layer R2 is not particularly limited, but is preferably 10 ppm / K or more, more preferably in the range of 10 ppm / K to 30 ppm / K, and more preferably in the range of 15 ppm / K to 25 ppm / K. If the CTE is less than 10 ppm / K or more than 30 ppm / K, warping occurs or dimensional stability decreases. The CTE can be controlled to the desired value by appropriately changing the combination of raw materials used, the thickness, and the drying and curing conditions.

[0054] When the insulating resin layer R1 and the insulating resin layer R2 are applied to, for example, a circuit board, in order to suppress deterioration of the dielectric loss, the dielectric loss tangent (Df) at 10 GHz is preferably 0.02 or less, more preferably in the range of 0.0005 to 0.01, and even more preferably in the range of 0.001 to 0.008. If the dielectric loss tangent at 10 GHz exceeds 0.02, when applied to a circuit board, inconveniences such as loss of electric signals on the transmission path of high-frequency signals are likely to occur. On the other hand, the lower limit of the dielectric loss tangent at 10 GHz is not particularly limited, but the physical property control as an insulating resin layer of a circuit board is taken into consideration.

[0055] When the insulating resin layer R1 and the insulating resin layer R2 are applied as insulating resin layers of a circuit board, for example, in order to ensure impedance matching, the relative dielectric constant (Dk) at 10 GHz is preferably 4.0 or less. If the relative dielectric constant at 10 GHz exceeds 4.0, when applied to a circuit board, this leads to deterioration of the dielectric loss of the insulating resin layer, and is likely to cause inconveniences such as loss of electrical signals on the transmission path of high-frequency signals.

[0056] <Preferable configuration of insulating resin layer> Polyimide is suitable for the insulating resin layer R1 and the insulating resin layer R2 in terms of heat resistance, dimensional stability, and chemical resistance. The insulating resin layer R1 and the insulating resin layer R2 preferably include a non-thermoplastic polyimide layer made of non-thermoplastic polyimide as a base resin layer. In addition, the insulating resin layer R1 and the insulating resin layer R2 preferably have a thermoplastic polyimide layer made of thermoplastic polyimide as a layer in contact with the adhesive layer AD in order to ensure adhesion with the adhesive layer AD. Furthermore, the insulating resin layer R1 and the insulating resin layer R2 preferably have a thermoplastic polyimide layer made of thermoplastic polyimide as a layer in contact with the metal layers M1 and M2 in terms of ensuring adhesion with the metal layers M1 and M2. In other words, the insulating resin layer R1 and the insulating resin layer R2 preferably have a layer structure of thermoplastic polyimide layer / non-thermoplastic polyimide layer / thermoplastic polyimide layer, respectively. In addition, the term "non-thermoplastic polyimide" generally refers to a polyimide that does not soften or exhibit adhesiveness even when heated. In the present invention, however, the term "non-thermoplastic polyimide" refers to a polyimide having a storage modulus of 1.0×10 at 30° C. as measured using a dynamic mechanical analyzer (DMA). 9 Pa or more, and the storage modulus at 300°C is 3.0×10 8 In addition, the term "thermoplastic polyimide" generally refers to a polyimide whose glass transition temperature (Tg) can be clearly confirmed. In the present invention, however, the term "thermoplastic polyimide" refers to a polyimide whose storage modulus at 30° C. measured by DMA is 1.0×10 8 Pa or more, and the storage modulus at 300°C is 3.0×10 7 This refers to polyimides with a modulus of less than Pa.

[0057] The non-thermoplastic polyimide constituting the non-thermoplastic polyimide layer contains an acid dianhydride residue and a diamine residue. The non-thermoplastic polyimide may contain, as the acid dianhydride residue and the diamine residue, an acid dianhydride residue derived from a tetracarboxylic dianhydride and a diamine residue derived from a diamine compound that are generally used as raw materials for non-thermoplastic polyimides. The thermoplastic polyimide constituting the thermoplastic polyimide layer contains an acid dianhydride residue and a diamine residue. The thermoplastic polyimide may contain, as the acid dianhydride residue and the diamine residue, an acid dianhydride residue derived from a tetracarboxylic dianhydride and a diamine residue derived from a diamine compound that are generally used as raw materials for thermoplastic polyimides. In non-thermoplastic polyimides and thermoplastic polyimides, the thermal expansion coefficient, tensile modulus, glass transition temperature, etc. can be controlled by selecting the types of the acid dianhydride residues and diamine residues, and the molar ratios of the respective types when two or more types of acid dianhydride residues or diamine residues are used. In non-thermoplastic polyimides and thermoplastic polyimides, when a plurality of polyimide structural units are present, they may be present as blocks or randomly, but are preferably present randomly.

[0058] <Adhesive layer> The resin constituting the adhesive layer AD is preferably, for example, polyimide, and more preferably aliphatic polyimide using aliphatic diamine as a raw material. The aliphatic polyimide is a solvent-soluble thermoplastic polyimide obtained by reacting an acid dianhydride component with a diamine component containing an aliphatic diamine. As the acid dianhydride component serving as the raw material of aliphatic polyimides, monomers generally used in the synthesis of thermoplastic polyimides can be used, such as 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA), 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride (DSDA), 4,4'-oxydiphthalic anhydride (ODPA), 4,4'-(hexafluoroisopropylidene)diphthalic anhydride (6FDA), 2,2-bis[4-(3,4-dicarboxyphenoxy)phenyl]propane dianhydride (BPADA), p-phenylenebis(trimellitic acid monoester acid anhydride) (TAHQ), ethylene glycol, etc. Aromatic acid dianhydrides such as bisanhydrotrimellitate (TMEG), 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), and 2,3',3,4'-biphenyltetracarboxylic dianhydride are preferred, and 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA) is more preferred. The aliphatic polyimide preferably contains 90 mol % or more of acid dianhydride residues derived from one or more of the above aromatic acid dianhydrides relative to the total acid dianhydride residues.

[0059] As the diamine component serving as the raw material of the aliphatic polyimide, a monomer generally used in the synthesis of a thermoplastic polyimide can be used, but from the viewpoint of lowering the dielectric tangent and improving the dielectric properties, it is preferable to use a dimer acid type diamine. That is, the aliphatic polyimide preferably contains 20 molar parts or more, more preferably 40 molar parts or more, and most preferably 60 molar parts or more of the diamine residue derived from the dimer acid type diamine relative to the total 100 molar parts of the diamine residue. By containing the diamine residue derived from the dimer acid type diamine in the above amount, the adhesive layer AD can have a lower glass transition temperature (lower Tg) to improve the thermocompression bonding characteristics, and can further reduce the internal stress due to the lower elastic modulus to improve the dielectric characteristics of the adhesive layer AD. If the content of the diamine residue derived from the dimer acid type diamine relative to the total diamine residue is less than 20 molar parts, the transmission loss during high frequency transmission may increase, or sufficient adhesion may not be obtained between the insulating resin layer R1 and the insulating resin layer R2.

[0060] The dimer acid diamine is a mixture containing the following component (a) as a main component and optionally containing components (b) and (c), and it is preferable to use a purified product in which the amounts of components (b) and (c) are controlled. (a) Dimer diamine (b) A monoamine compound obtained by substituting the terminal carboxylic acid group of a monobasic acid compound having 10 to 40 carbon atoms with a primary aminomethyl group or an amino group. (c) Amine compounds obtained by substituting the terminal carboxylic acid group of a polybasic acid compound having a hydrocarbon group having 41 to 80 carbon atoms with a primary aminomethyl group or an amino group (excluding the above-mentioned dimer diamine).

[0061] The dimer diamine of the component (a) means a diamine in which two terminal carboxylic acid groups (-COOH) of a dimer acid are replaced by primary aminomethyl groups (-CH2-NH2) or amino groups (-NH2). Dimer acid is a known dibasic acid obtained by intermolecular polymerization of unsaturated fatty acids, and its industrial production process is almost standardized in the industry, and is obtained by dimerizing unsaturated fatty acids having 11 to 22 carbon atoms using a clay catalyst or the like. Industrially obtained dimer acid is mainly composed of a dibasic acid having 36 carbon atoms obtained by dimerizing unsaturated fatty acids having 18 carbon atoms, such as oleic acid, linoleic acid, and linolenic acid, but contains any amount of monomer acid (having 18 carbon atoms), trimer acid (having 54 carbon atoms), and other polymerized fatty acids having 20 to 54 carbon atoms depending on the degree of purification. In addition, although double bonds remain after the dimerization reaction, in the present invention, those which have been further subjected to a hydrogenation reaction to reduce the degree of unsaturation are also included in the dimer acid. The dimer diamine of component (a) can be defined as a diamine compound obtained by substituting the terminal carboxylic acid group of a dibasic acid compound having 18 to 54 carbon atoms, preferably 22 to 44 carbon atoms, with a primary aminomethyl group or an amino group.

[0062] The dimer acid diamine to be used is one in which the dimer diamine content of component (a) is increased to 96% by weight or more, preferably 97% by weight or more, and more preferably 98% by weight or more by a purification method such as molecular distillation. By increasing the dimer diamine content of component (a) to 96% by weight or more, the broadening of the molecular weight distribution of the polyimide can be suppressed. If technically possible, it is best that all of the dimer acid diamine (100% by weight) is composed of the dimer diamine of component (a).

[0063] Commercially available dimer acid diamines can be used, such as PRIAMINE 1073 (trade name), PRIAMINE 1074 (trade name), and PRIAMINE 1075 (trade name) manufactured by Croda Japan. When using these commercially available products, it is preferable to purify them in order to reduce the amount of components other than the dimer diamine of component (a), and for example, it is preferable to make the dimer diamine content 96% by weight or more. There are no particular limitations on the purification method, but known methods such as distillation and precipitation purification are suitable.

[0064] For the aliphatic polyimide, an acid dianhydride component other than the above-mentioned acid dianhydrides and a diamine component other than the dimer acid diamine can be used as a raw material within a range that does not impair the effects of the invention. In the aliphatic polyimide, the thermal expansion coefficient, glass transition temperature, dielectric properties, etc. can be controlled by selecting the types of the acid dianhydride component and the diamine component, and the respective molar ratios when two or more types of acid dianhydrides or diamines are used.

[0065] The weight-average molecular weight of the aliphatic polyimide is preferably within the range of 10,000 to 400,000, more preferably within the range of 20,000 to 350,000. If the weight-average molecular weight is less than 10,000, the strength of the adhesive layer AD tends to decrease and become brittle. On the other hand, if the weight-average molecular weight exceeds 400,000, the viscosity increases excessively, and defects such as uneven thickness and streaks in the adhesive layer AD tend to occur during the coating process.

[0066] The aliphatic polyimide is most preferably a completely imidized structure. However, a part of the polyimide may be an amic acid. The imidization rate can be determined by measuring the infrared absorption spectrum of a polyimide thin film by a single reflection ATR method using a Fourier transform infrared spectrophotometer (commercially available: FT / IR620 manufactured by JASCO Corporation) at 1015 cm -1 Based on the benzene ring absorber near 1780cm -1 It can be calculated from the absorbance of the C=O stretching derived from the imide group.

[0067] The glass transition temperature (Tg) of the aliphatic polyimide is preferably 250° C. or lower, and more preferably within the range of 40° C. to 200° C. When the Tg of the aliphatic polyimide is 250° C. or lower, thermocompression bonding can be performed at a low temperature, thereby mitigating the internal stress generated during lamination and suppressing dimensional changes after circuit processing.

[0068] Aliphatic polyimides can be cured by reacting the ketone groups in the polymer chain with the amino groups of an amino compound having at least two primary amino groups as functional groups to form a crosslinked structure with a C=N bond by thermal condensation. The formation of the crosslinked structure can improve the heat resistance of the aliphatic polyimide. A preferred tetracarboxylic anhydride for forming an aliphatic polyimide having a ketone group is, for example, 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA), and a preferred diamine compound is, for example, an aromatic diamine such as 4,4'-bis(3-aminophenoxy)benzophenone (BABP) or 1,3-bis[4-(3-aminophenoxy)benzoyl]benzene (BABB).

[0069] Examples of amino compounds that can be used to crosslink aliphatic polyimides include dihydrazide compounds, aromatic diamines, and aliphatic amines. Among these, dihydrazide compounds are preferred. Aliphatic amines other than dihydrazide compounds are prone to form crosslinked structures even at room temperature, which raises concerns about the storage stability of the varnish, while aromatic diamines require high temperatures to form crosslinked structures. When a dihydrazide compound is used, it is possible to achieve both the storage stability of the varnish and a shortened curing time. Examples of dihydrazide compounds include oxalic acid dihydrazide, malonic acid dihydrazide, succinic acid dihydrazide, glutaric acid dihydrazide, adipic acid dihydrazide, pimelic acid dihydrazide, suberic acid dihydrazide, azelaic acid dihydrazide, sebacic acid dihydrazide, dodecanedioic acid dihydrazide, maleic acid dihydrazide, fumaric acid dihydrazide, diglyceryl ester dihydrazide, ... Preferred are dihydrazide compounds such as cholic acid dihydrazide, tartaric acid dihydrazide, malic acid dihydrazide, phthalic acid dihydrazide, isophthalic acid dihydrazide, terephthalic acid dihydrazide, 2,6-naphthoic acid dihydrazide, 4,4-bisbenzene dihydrazide, 1,4-naphthoic acid dihydrazide, 2,6-pyridine diacid dihydrazide, itaconic acid dihydrazide, etc. The above dihydrazide compounds may be used alone or in combination of two or more.

[0070] When crosslinking an aliphatic polyimide, the above amino compound is added to a resin solution containing an aliphatic polyimide having a ketone group, and the ketone group in the aliphatic polyimide and the primary amino group of the amino compound undergo a condensation reaction. This condensation reaction hardens the resin solution to form a hardened product.

[0071] The conditions of the condensation reaction for forming crosslinks are not particularly limited as long as the ketone group in the aliphatic polyimide reacts with the primary amino group of the amino compound to form an imine bond (C=N bond). The temperature of the heat condensation is preferably within the range of, for example, 120 to 220°C, more preferably within the range of 140 to 200°C, in order to release water produced by condensation outside the system. The end point of the reaction can be determined by measuring the infrared absorption spectrum using, for example, a Fourier transform infrared spectrophotometer (commercially available: FT / IR620 manufactured by JASCO Corporation) at 1670 cm -1 The decrease or disappearance of the absorption peak due to the ketone group in the polyimide resin near 1635 cm -1 This can be confirmed by the appearance of an absorption peak derived from a nearby imine group.

[0072] The crosslinking reaction by thermal condensation between the ketone groups of the aliphatic polyimide and the primary amino groups of the amino compound can be allowed to proceed to a certain degree of crosslinking in step 2, for example, by applying an aliphatic polyimide resin composition to which an amino compound has been added onto the insulating resin layer R1 of the first metal-clad laminate C1 or onto the insulating resin layer R2 of the second metal-clad laminate C1, or onto the substrate, and drying the composition. In step 3, the crosslinking reaction is preferably allowed to proceed until it is completed (the degree of crosslinking is approximately 100%).

[0073] By using the above aliphatic polyimide, the adhesive layer AD has excellent flexibility, heat resistance and dielectric properties (low dielectric constant and low dielectric loss tangent).

[0074] In addition, in order to provide heat resistance to the aliphatic polyimide, the formation of imine bonds has been described as the formation of a crosslinked structure, but the present invention is not limited to this. An organic peroxide, a curing agent, a curing accelerator, etc. may be used for the crosslinking of the adhesive layer AD, and if necessary, a curing agent and a curing accelerator, or a catalyst and a co-catalyst may be used in combination.

[0075] (Filler) The adhesive layer AD contains a metal salt of an organic phosphinic acid as a filler component. The metal salt of an organic phosphinic acid is a flame retardant that does not reduce the dielectric properties of the polyimide, but has the effect of improving the adhesion between layers when mixed at a high concentration. In order to fully exert such an effect, preferably 80% by weight or more, more preferably 90% by weight or more, and most preferably 95 to 100% by weight of the filler component is a metal salt of an organic phosphinic acid. As the metal salt of an organic phosphinic acid, for example, an aluminum salt of an organic phosphinic acid represented by the following general formula (F1) is preferable.

[0076] [ka]

[0077] In the general formula (F1), two R's each independently represent an alkyl group, and R is preferably a lower alkyl group having 1 to 4 carbon atoms.

[0078] Metal salts of organic phosphinic acid have an average particle diameter (D 50 ) is preferably within the range of 1.0 to 3.0 μm, and the ratio of particles having a particle diameter exceeding 10 μm is 1 vol % or less. If the ratio of particles having a particle diameter exceeding 10 μm exceeds 1 vol %, the filler particle diameter in the adhesive layer AD becomes large, and the filler becomes likely to fall off during cutting or drilling. As the metal salt of the above-mentioned organic phosphinic acid, commercially available products can be used, for example, Exolit OP945 (trade name, manufactured by Clariant).

[0079] From the viewpoint of ensuring the adhesion between the adhesive layer AD and the insulating resin layer R1 and the insulating resin layer R2, the weight ratio of the metal salt of organic phosphinic acid to the entire adhesive layer AD is in the range of 28% by weight to 47% by weight, and preferably in the range of 30% by weight to 40% by weight. If the weight ratio of the metal salt of organic phosphinic acid is less than 28% by weight, the adhesion between the adhesive layer AD and the insulating resin layers R1 and R2 is not sufficiently exhibited, and if it exceeds 47% by weight, the elongation when the adhesive layer AD is formed may decrease or the dielectric properties may deteriorate. From the same viewpoint, the weight ratio of the metal salt of organic phosphinic acid to the total amount of 100 parts by weight of the resin content is preferably in the range of more than 40 parts by weight to 90 parts by weight, more preferably in the range of more than 40 parts by weight to 80 parts by weight, and most preferably in the range of 45 parts by weight to 70 parts by weight. If the weight ratio of the metal salt of organic phosphinic acid is 40 parts by weight or less, the adhesion between the layers may not be sufficiently exhibited, and if it exceeds 90 parts by weight, the elongation of the adhesive layer AD may decrease or the dielectric properties may deteriorate. The reason why the adhesion between the adhesive layer AD and the insulating resin layer R1 and the insulating resin layer R2 is improved by setting the content of the metal salt of organic phosphinic acid within the above range is presumably because, when peel-off stress is applied, crazes (fine cracks) originating from the filler in the resin release the strain within the resin and alleviate stress concentration. In addition, since the concentration of the particulate filler component is increased, aggregation occurs, and therefore it becomes necessary to compound a large amount of dispersant. However, since the dispersant has an adverse effect on the dielectric properties, it has been difficult to achieve both low dielectric tangent and high concentration of the filler component. In the present invention, as described above, in the process of producing the resin composition, the polyimide and the metal salt of the organic phosphinic acid are mixed in multiple stages, thereby realizing high concentration compounding of the metal salt of the organic phosphinic acid of more than 40 parts by weight per 100 parts by weight of the total amount of the resin content without necessarily using a dispersant.

[0080] In addition, from the viewpoint of fully exerting the effects of the invention, the total amount of the resin component and the metal salt of the organic phosphinic acid is preferably 80% by weight or more, more preferably 90% by weight or more, and most preferably 95 to 100% by weight, based on the total solid content in the adhesive layer AD.

[0081] In addition, the adhesive layer AD may contain a filler other than the metal salt of organic phosphinic acid, if necessary. Examples of the filler include silicon dioxide, aluminum oxide, magnesium oxide, beryllium oxide, boron nitride, aluminum nitride, silicon nitride, aluminum fluoride, calcium fluoride, etc. These may be used alone or in combination of two or more.

[0082] (CTE of adhesive layer) The thermoplastic or thermosetting resin constituting the adhesive layer AD has high thermal expansion but low elasticity and a low glass transition temperature, so that even if the CTE exceeds 30 ppm / K, the internal stress generated during lamination can be alleviated. Therefore, the CTE of the adhesive layer AD is preferably 35 ppm / K or more, more preferably in the range of 35 ppm / K to 200 ppm / K, and even more preferably in the range of 35 ppm / K to 150 ppm / K. The adhesive layer AD can be made to have a desired CTE by appropriately changing the combination of raw materials used, the thickness, and the drying and curing conditions.

[0083] (Dielectric tangent of adhesive layer) In order to suppress the deterioration of dielectric loss when applied to a circuit board, for example, the adhesive layer AD has a dielectric loss tangent (Df) at 10 GHz of preferably 0.004 or less, more preferably 0.003 or less, and even more preferably 0.002 or less. If the dielectric loss tangent at 10 GHz of the adhesive layer AD exceeds 0.004, when applied to a circuit board, problems such as loss of electrical signals on the transmission path of high-frequency signals are likely to occur. On the other hand, the lower limit of the dielectric loss tangent at 10 GHz of the adhesive layer AD is not particularly limited.

[0084] (Dielectric constant of adhesive layer) In order to ensure impedance matching, the adhesive layer AD preferably has a relative dielectric constant (Dk) of 4.0 or less at 10 GHz when applied to a circuit board, for example. If the relative dielectric constant of the adhesive layer AD at 10 GHz exceeds 4.0, the adhesive layer AD may have a deteriorated dielectric loss when applied to a circuit board, which may easily cause problems such as loss of electrical signals on the transmission path of high-frequency signals.

[0085] <Layer thickness> In the double-sided metal-clad laminate C, the resin laminate consisting of the insulating resin layer R1, the adhesive layer AD, and the insulating resin layer R2 has a total thickness T1 that is preferably within a range of, for example, 70 to 500 μm, and more preferably within a range of 100 to 300 μm. If the total thickness T1 is less than 70 μm, the effect of reducing transmission loss when used in a circuit board becomes insufficient, and if it exceeds 500 μm, there is a risk of reduced productivity. The ratio (T2 / T1) of the thickness T2 of the adhesive layer AD to the total thickness T1 is preferably within a range of, for example, 0.3 to 0.96, and more preferably within a range of 0.5 to 0.7. If the ratio (T2 / T1) is less than 0.3, it becomes difficult to achieve a low dielectric tangent of the resin laminate, and if it exceeds 0.96, problems such as reduced dimensional stability occur.

[0086] In the double-sided metal-clad laminate C, the thickness T2 of the adhesive layer AD is preferably, for example, within the range of 25 to 450 μm, and more preferably within the range of 50 to 250 μm. If the thickness T2 of the adhesive layer AD is less than the above lower limit, the transmission loss may increase as a high-frequency substrate. On the other hand, if the thickness of the adhesive layer AD exceeds the above upper limit, problems such as reduced dimensional stability may occur. According to the method of the present invention, it is possible to avoid adverse effects due to residual condensation water resulting from the crosslinking reaction of the thermal crosslinkable resin in the adhesive layer AD, and therefore it is possible to maximize the thickness T2 of the adhesive layer AD and its ratio (T2 / T1) while maintaining a low dielectric tangent.

[0087] In the double-sided metal-clad laminate C, the thickness T3 of the insulating resin layer R1 and the insulating resin layer R2 is preferably in the range of, for example, 12 to 100 μm, and more preferably in the range of 12 to 50 μm. If the thickness T3 of the insulating resin layer R1 and the insulating resin layer R2 is less than the above lower limit, problems such as warping of the double-sided metal-clad laminate C may occur. If the thickness T3 of the insulating resin layer R1 and the insulating resin layer R2 exceeds the above upper limit, problems such as reduced productivity may occur. Note that the insulating resin layer R1 and the insulating resin layer R2 do not necessarily have to have the same thickness.

[0088] <Adhesion between insulating resin layer and adhesive layer> In the double-sided metal-clad laminate C, the interlayer adhesion between the insulating resin layer R1 and the adhesive layer AD, and the interlayer adhesion between the insulating resin layer R2 and the adhesive layer AD, are preferably 1.0 kN / m or more, more preferably 1.1 kN / m or more, in terms of peel strength. The peel strength can be measured by the method and conditions shown in the Examples below. If the peel strength is less than 1.0 kN / m, delamination is likely to occur during circuit processing such as drilling and cutting, leading to deterioration in the processing yield and reliability of the circuit board.

[0089] [Circuit board manufacturing method] By etching or otherwise processing the metal layer M1 and / or metal layer M2 of the double-sided metal-clad laminate C of this embodiment obtained as described above into a wiring circuit, a circuit board such as a single-sided FPC or a double-sided FPC can be manufactured. EXAMPLES

[0090] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the following examples, various measurements and evaluations were performed according to the following methods, unless otherwise specified.

[0091] [Peel strength measurement] The double-sided metal-clad laminate was cut into a test piece with a width of 0.5 mm and a length of 70 mm, and one of the copper foil surfaces was fixed to an aluminum plate with double-sided tape. The adhesive layer and the insulating layer were peeled off using a Tensilon tester (manufactured by Toyo Seiki Seisakusho, product name: Strograph VE-1D) to measure the peel strength. The other laminate consisting of the copper foil and insulating resin layer, which was not fixed, was pulled in the 180° direction at a speed of 50 mm / min, and the median strength when 10 mm was peeled off was obtained, which was taken as the peel strength.

[0092] [Viscosity measurement] The viscosity was measured at 25° C. using an E-type viscometer (manufactured by Brookfield, product name: DV-II+Pro). The rotation speed was set so that the torque was 10% to 90%, and the value was read when the viscosity stabilized 2 minutes after the start of the measurement.

[0093] [Measurement of weight average molecular weight (Mw)] The weight average molecular weight was measured by gel permeation chromatography (manufactured by Tosoh Corporation, product name: HLC-8220GPC was used). Polystyrene was used as a standard substance, and tetrahydrofuran (THF) was used as a developing solvent.

[0094] [Measurement of storage modulus and glass transition temperature (Tg)] The storage modulus was measured on a polyimide film measuring 5 mm x 70 mm using a dynamic viscoelasticity measuring device (DMA: manufactured by TA Instruments, product name: RSA G2) at a heating rate of 4°C / min from 30°C to 400°C and a frequency of 1 Hz. The peak value of Tan δ at the maximum temperature during the measurement was defined as the glass transition temperature (Tg). The storage modulus at 30°C measured using DMA was 1.0×10 8 Pa or more, and the storage modulus at 300°C is 3.0×10 7 Those with a storage modulus of less than 1.0 x 10 Pa at 30°C are considered "thermoplastic" and 9 Pa or more, and the storage modulus at 300°C is 3.0×10 8 Those showing a strength of 100 Pa or more were categorized as "non-thermoplastic."

[0095] The abbreviations used in the examples and comparative examples represent the following compounds. BTDA: 3,3',4,4'-benzophenonetetracarboxylic dianhydride BPDA: 3,3',4,4'-biphenyltetracarboxylic dianhydride PMDA: Pyromellitic dianhydride DDA: aliphatic diamine having 36 carbon atoms [manufactured by Croda Japan Co., Ltd., product name: PRIAMINE 1074, distilled and purified, amine value: 210 mg KOH / g, mixture of dimer diamines having cyclic and chain structures, component (a): 97.9%, component (b): 0.3%, component (c): 1.8%] The "%" for component (a), component (b), and component (c) refer to the area percentage of the chromatogram in the GPC measurement. The molecular weight of DDA was calculated using the following formula. Molecular weight = 56.1 x 2 x 1000 / amine value] m-TB: 2,2'-dimethyl-4,4'-diaminobiphenyl TPE-R: 1,3-bis(4-aminophenoxy)benzene Bisaniline-M: 1,3-bis[2-(4-aminophenyl)-2-propyl]benzene N-12: Dodecanedioic acid dihydrazide NMP: N-methyl-2-pyrrolidone DMAc: N,N-dimethylacetamide OP945: organic phosphinic acid aluminum salt (manufactured by Clariant Japan, trade name: Exolit OP945, D 50 ;2.1μm, D 95 3.0 μm, maximum particle size: 6.7 μm, percentage of particles with a size exceeding 10 μm: 0% by volume

[0096] (Synthesis Example 1) <Preparation of resin solution for adhesive layer> Under a nitrogen stream, a polyamic acid solution was prepared by charging a reaction vessel with 45.43 parts by weight of BTDA (0.1410 parts by mole), 74.57 parts by weight of DDA (0.1396 parts by mole), 168 parts by weight of NMP, and 112 parts by weight of xylene, and mixing thoroughly for 1 hour at 40° C. The polyamic acid solution was heated to 190° C., heated and stirred for 5 hours, and 98 parts by weight of xylene was added to complete the imidization, preparing polyimide solution 1 (solid content: 30% by weight, weight average molecular weight: 52,800).

[0097] (Synthesis Example 2) <Preparation of polyamic acid solution for insulating resin layer> Under a nitrogen stream, 64.20 g of m-TB (0.302 mol), 5.48 g of bisaniline-M (0.016 mol), and DMAc in an amount that would result in a solids concentration of 15% by weight after polymerization were added to the reaction vessel and stirred at room temperature to dissolve. Next, 34.20 g of PMDA (0.157 mol) and 46.13 g of BPDA (0.157 mol) were added, and the polymerization reaction was continued by stirring at room temperature for 3 hours to prepare polyamic acid solution 1 (viscosity: 26,500 mPa s). The storage modulus of the polyimide film prepared using polyamic acid solution 1 was measured and determined to be "non-thermoplastic."

[0098] (Synthesis Example 3) <Preparation of polyamic acid solution for insulating resin layer> After adding 69.56 g of m-TB (0.328 mol), 542.75 g of TPE-R (1.857 mol), DMAc in an amount that would result in a solids concentration of 12 wt% after polymerization, 194.39 g of PMDA (0.891 mol), and 393.31 g of BPDA (1.337 mol), the mixture was stirred at room temperature for 3 hours to carry out the polymerization reaction, preparing polyamic acid solution 2 (viscosity: 2,650 mPa s). The storage modulus of the polyimide film prepared using polyamic acid solution 2 was measured and determined to be "thermoplastic".

[0099] (Combination example 1) 9.40 parts by weight of N-12 was mixed with 100.00 parts by weight of polyimide solution 1, diluted with 143.23 parts by weight of OP945 (55.00 parts by weight for a total of 100 parts by weight of the final resin content), 95.44 parts by weight of xylene, and 17.18 parts by weight of NMP, and stirred with a planetary mixer. Then, 768.06 parts by weight of polyimide solution 1 and 36.78 parts by weight of xylene were added and stirred for 2 hours to prepare resin composition 1 (viscosity: 2,477 mPa s).

[0100] (Combination example 2) 9.40 parts by weight of N-12 was mixed with 100.00 parts by weight of polyimide solution 1, diluted with 156.25 parts by weight of OP945 (60.00 parts by weight for a total of 100 parts by weight of the final resin content), 106.89 parts by weight of xylene, and 18.76 parts by weight of NMP, and stirred with a planetary mixer. Then, 768.06 parts by weight of polyimide solution 1 and 37.46 parts by weight of xylene were added and stirred for 2 hours to prepare resin composition 2 (viscosity: 2,405 mPa s).

[0101] (Combination example 3) 9.40 parts by weight of N-12 was mixed with 100.00 parts by weight of polyimide solution 1, diluted with 169.27 parts by weight of OP945 (65.00 parts by weight for a total of 100 parts by weight of the final resin content), 119.55 parts by weight of xylene, and 19.11 parts by weight of NMP, and stirred with a planetary mixer. Then, 768.06 parts by weight of polyimide solution 1 and 22.55 parts by weight of xylene were added and stirred for 2 hours to prepare resin composition 3 (viscosity: 2,461 mPa s).

[0102] (Combination example 4) 9.40 parts by weight of N-12 was mixed with 100.00 parts by weight of polyimide solution 1, diluted with 65.10 parts by weight of OP945 (25.00 parts by weight for a total of 100 parts by weight of the final resin content), 18.65 parts by weight of xylene, and 15.85 parts by weight of NMP, and stirred with a planetary mixer. Then, 768.06 parts by weight of polyimide solution 1 and 103.02 parts by weight of xylene were added and stirred for 2 hours to prepare resin composition 4 (viscosity: 2,151 mPa s).

[0103] (Combination example 5) 9.40 parts by weight of N-12 was mixed with 100.00 parts by weight of polyimide solution 1, and then 91.15 parts by weight of OP945 (35.00 parts by weight for a total of 100 parts by weight of the final resin content), 46.37 parts by weight of xylene, and 14.17 parts by weight of NMP were added to dilute and stir using a planetary mixer. Then, 768.06 parts by weight of polyimide solution 1 and 62.69 parts by weight of xylene were added and stirred for 2 hours to prepare resin composition 5 (viscosity: 2,455 mPa s).

[0104] (Example 1) <Preparation of single-sided metal-clad laminate 1> On the electrolytic copper foil (thickness: 12 μm, surface roughness Rz of the resin layer side: 0.6 μm), polyamic acid solution 2 was uniformly applied so that the thickness after curing was about 2 to 3 μm, and then heated and dried at 120 ° C to remove the solvent. Next, polyamic acid solution 1 was uniformly applied thereon so that the thickness after curing was about 16 μm, and then heated and dried at 120 ° C to remove the solvent. Furthermore, polyamic acid solution 2 was uniformly applied thereon so that the thickness after curing was about 2 to 3 μm, and then heated and dried at 120 ° C to remove the solvent, and a single-sided metal-clad laminate 1' was prepared. The single-sided metal-clad laminate 1' was subjected to stepwise heat treatment from 120 ° C to 360 ° C to complete imidization, form an insulating resin layer, and prepare a single-sided metal-clad laminate 1.

[0105] [Example 1] <Preparation of double-sided metal-clad laminate 1> Resin composition 1 was uniformly applied onto the insulating resin layer of single-sided metal-clad laminate 1 so that the thickness after drying was 60 μm, and the temperature was raised from 80 ° C to 160 ° C, and the mixture was dried for 6 minutes and heat-treated for crosslinking to form a metal-clad laminate 1 with a filler-containing layer. The weight ratio of OP945 to the entire filler-containing layer was 35 wt%. A metal-clad laminate 2 with a filler-containing layer was prepared in the same manner as for the metal-clad laminate 1 with a filler-containing layer, and the filler-containing layers were arranged so as to face each other and temporarily pressed at 80 ° C, 0.5 MPa, and for 2 seconds to prepare a primary laminate 1. The primary laminate 1 was heat-treated at 180 ° C for 120 hours in a thermostatic chamber to form an adhesive layer 1, and a double-sided metal-clad laminate 1 was obtained. The peel strength between the adhesive layer 1 and the single-sided metal-clad laminate 1 on the side of the metal-clad laminate 2 with a filler-containing layer was evaluated to be 1.00 kN / m.

[0106] [Example 2] <Preparation of double-sided metal-clad laminate 2> A primary laminate 2 and a double-sided metal-clad laminate 2 were obtained in the same manner as in Example 1, except that resin composition 2 was used. The weight ratio of OP945 to the entire filler-containing layer was 38% by weight. The peel strength was evaluated to be 1.13 kN / m.

[0107] [Example 3] <Preparation of double-sided metal-clad laminate 3> A primary laminate 3 and a double-sided metal-clad laminate 3 were obtained in the same manner as in Example 1, except that resin composition 3 was used. The weight ratio of OP945 to the entire filler-containing layer was 39% by weight. The peel strength was evaluated to be 1.14 kN / m.

[0108] Comparative Example 1 <Preparation of double-sided metal-clad laminate 4> A primary laminate 4 and a double-sided metal-clad laminate 4 were obtained in the same manner as in Example 1, except that resin composition 4 was used. The weight ratio of OP945 to the entire filler-containing layer was 20% by weight. The peel strength was evaluated to be 0.85 kN / m.

[0109] Comparative Example 2 <Preparation of double-sided metal-clad laminate 5> A primary laminate 5 and a double-sided metal-clad laminate 5 were obtained in the same manner as in Example 1, except that resin composition 5 was used. The weight ratio of OP945 to the entire filler-containing layer was 26% by weight. The peel strength was evaluated to be 0.89 kN / m.

[0110] Reference example 1 <Preparation of double-sided metal-clad laminate 6> The resin composition 1 was uniformly applied onto the insulating resin layer of the single-sided metal-clad laminate 1 so that the thickness after drying was 60 μm, and the temperature was raised stepwise from 80 ° C. to 160 ° C. for 6 minutes to form an adhesive layer 6 by heat treatment for drying and crosslinking, and a metal-clad laminate 1 with an adhesive layer was formed. Thereafter, another single-sided metal-clad laminate 1 was placed on the surface of the adhesive layer 6 formed with the resin composition 1 so that the surface of the insulating resin layer side was in contact with the surface of the adhesive layer 6 formed with the resin composition 1, and temporarily pressed at 80 ° C., 0.5 MPa, and for 2 seconds to prepare a primary laminate 6. The primary laminate 6 was heat-treated in a thermostatic chamber at 180 ° C. for 120 hours to obtain a double-sided metal-clad laminate 6. The peel strength between the adhesive layer 6 formed with the resin composition 1 and the insulating resin layer of the single-sided metal-clad laminate 1 laminated later was evaluated to be 0.85 kN / m.

[0111] Although the embodiment of the present invention has been described in detail above for the purpose of illustration, the present invention is not limited to the above embodiment, and various modifications are possible. [Explanation of symbols]

[0112] AD: adhesive layer; AD1, AD2: filler-containing layer; C: double-sided metal-clad laminate; C1: first metal-clad laminate; C2: second metal-clad laminate; C1', C2': metal-clad laminate with filler-containing layer; M1, M2: metal layer; R1, R2: insulating resin layer

Claims

1. A method for producing a double-sided metal-clad laminate in which metal layers are laminated on both sides of a resin laminate having an adhesive layer and an insulating resin layer, comprising the steps of: Steps 1 to 3 below: Process 1: A step of preparing a single-sided metal-clad laminate having a metal layer and an insulating resin layer laminated on at least one surface of the metal layer; Process 2: laminating a filler-containing layer on a surface of the insulating resin layer in the single-sided metal-clad laminate to produce a metal-clad laminate with a filler-containing layer; Step 3: a step of forming the adhesive layer by laminating two of the metal-clad laminates with the filler-containing layer so that the filler-containing layers face each other, thereby forming a double-sided metal-clad laminate having metal layers on both sides of the resin laminate; Including, the filler-containing layer comprises a polyimide containing a tetracarboxylic acid residue and a diamine residue, and a metal salt of an organic phosphinic acid; the polyimide contains 20 or more molar parts of a diamine residue derived from a dimer acid type diamine in which two terminal carboxylic acid residues of a dimer acid are substituted with a primary aminomethyl group or an amino group, relative to a total of 100 molar parts of the diamine residue; A method for producing a double-sided metal-clad laminate, characterized in that a weight ratio of the metal salt of an organic phosphinic acid to the entire filler-containing layer is within a range of 28% by weight or more and 47% by weight or less.

2. 2. The method for producing a double-sided metal-clad laminate according to claim 1, characterized in that the filler-containing layer in step 2 is formed by applying and drying a resin composition containing the polyimide and the metal salt of the organic phosphinic acid to the surface of the insulating resin layer.

3. The resin composition is subjected to the following steps (i) and (ii); (i) mixing a portion of the polyimide with the metal salt of the organic phosphinic acid in an organic solvent and stirring to obtain a filler-dispersed resin solution; and (ii) mixing the remainder of the polyimide with an organic solvent into the filler-dispersed resin solution and stirring to obtain the resin composition; Including, The method for producing a double-sided metal-clad laminate according to claim 2, characterized in that in step (i), the weight ratio of the polyimide in the filler-dispersed resin solution is within the range of 3 to 15 parts by weight relative to 100 parts by weight of the final total amount of the polyimide, and the solid content concentration in the filler-dispersed resin solution is adjusted to within the range of 40 to 60 parts by weight, and in step (ii), the weight ratio of the metal salt of the organic phosphinic acid in the resin composition is within the range of more than 40 parts by weight and not more than 90 parts by weight relative to 100 parts by weight of the final total amount of the polyimide.

4. The method for producing a double-sided metal-clad laminate according to claim 1 , wherein in the step 3, the two metal-clad laminates with the filler-containing layer are temporarily pressure-bonded together, and then a heat treatment is performed.

5. 2. The method for manufacturing a double-sided metal-clad laminate according to claim 1, characterized in that the insulating resin layer of the single-sided metal-clad laminate has a multilayer structure in which a thermoplastic polyimide layer, a non-thermoplastic polyimide layer, and a thermoplastic polyimide layer are laminated in this order.

6. The method for manufacturing a double-sided metal-clad laminate according to claim 1, wherein the resin laminate is formed by laminating an insulating resin layer / an adhesive layer / an insulating resin layer in that order, and the adhesive layer is formed by bonding two of the filler-containing layers together to form an integrated body.

7. A method for producing a circuit board, comprising the step of processing one or both of the metal layers in a double-sided metal-clad laminate produced by the method according to any one of claims 1 to 6 into wiring.

Citation Information

Patent Citations

  • Metal-clad laminate sheet and circuit board

    JP2018170417A

  • Metal-clad laminated plate and circuit board

    JP2020055299A

  • Metal-cladded laminate plate, and circuit board

    WO2020022129A1